2013
DOI: 10.1016/j.neuroimage.2013.05.041
|View full text |Cite
|
Sign up to set email alerts
|

The WU-Minn Human Connectome Project: An overview

Abstract: The Human Connectome Project consortium led by Washington University, University of Minnesota, and Oxford University is undertaking a systematic effort to map macroscopic human brain circuits and their relationship to behavior in a large population of healthy adults. This overview article focuses on progress made during the first half of the 5-year project in refining the methods for data acquisition and analysis. Preliminary analyses based on a finalized set of acquisition and preprocessing protocols demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
5,133
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 5,016 publications
(5,192 citation statements)
references
References 61 publications
47
5,133
0
12
Order By: Relevance
“…The results in this paper represent the foundations of a surface-constrained set of functional and diffusion analysis pipelines, inspired by frameworks proposed by the HCP (Glasser et al, 2013;Van Essen et al, 2013), and based on FreeSurfer methods for surface extraction (Fischl et al, 1999b;Fischl, 2012). Studies have shown that surface-constrained analyses: improve the localisation of functional units along the cortical surface Glasser et al, 2013Glasser et al, , 2016bVan Essen et al, 2012); reduce the mixing of white and grey matter fMRI signals during smoothing (Glasser et al, 2013); and increase the alignment of functional areas during registration (Durrleman et al, 2009;Fischl et al, 1999c;Lombaert et al, 2013;Robinson et al, 2014;Wright et al, 2015;Yeo et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…The results in this paper represent the foundations of a surface-constrained set of functional and diffusion analysis pipelines, inspired by frameworks proposed by the HCP (Glasser et al, 2013;Van Essen et al, 2013), and based on FreeSurfer methods for surface extraction (Fischl et al, 1999b;Fischl, 2012). Studies have shown that surface-constrained analyses: improve the localisation of functional units along the cortical surface Glasser et al, 2013Glasser et al, , 2016bVan Essen et al, 2012); reduce the mixing of white and grey matter fMRI signals during smoothing (Glasser et al, 2013); and increase the alignment of functional areas during registration (Durrleman et al, 2009;Fischl et al, 1999c;Lombaert et al, 2013;Robinson et al, 2014;Wright et al, 2015;Yeo et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Although continued development of prospective methods will improve the way that future studies use structural imaging to study anatomy [see Zaitsev et al, 2015], development of such innovations is not applicable to a number of extremely valuable legacy datasets and to many other on‐going large‐scale data collection initiatives [e.g., ABIDE, ADHD‐200, ADNI, Betula, DLBS, FCON1000, HCP, HABS, NIMH adolescents, PNC, SLS; ADHD‐200‐Consortium, 2012; Biswal et al, 2010; Chan et al, 2014; Dagley et al, 2015; Di Martino et al, 2014; Giedd et al, 1999; Jack et al, 2008; Nilsson et al, 1997, 2004; Park et al, 2012; Satterthwaite et al, 2014; Schaie and Willis, 2010; Van Essen et al, 2012b, 2013]. While many studies have led efforts to correct the motion‐related bias in EPI, less work has demonstrated a suitable technique for mitigating the motion‐related bias on T1w imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the Hammersmith and Queen Charlotte's and Chelsea Research ethics committee. For the structural connectivity analysis, the first ten subjects from the Human Connectome Project [Van Essen et al, 2013] were included (5 male, age range 22–35). The preprocessed version of the data was used [Glasser et al, 2013].…”
Section: Methodsmentioning
confidence: 99%